Antitumor effects and molecular mechanisms of ponatinib on endometrial cancer cells harboring activating FGFR2 mutations. Issue 1 (2nd January 2016) - Kim, Do-Hee; Kwak, Yeonui; Kim, Nam Doo; Sim, Taebo
ABSTRACT: Aberrant mutational activation of FGFR2 is associated with endometrial cancers (ECs). AP24534 (ponatinib) currently undergoing clinical trials has been known to be an orally available multi-targeted tyrosine kinase inhibitor. Our biochemical kinase assay showed that AP24534 is potent against wild-type FGFR1-4 and 5 mutant FGFRs (V561M-FGFR1, N549H-FGFR2, K650E-FGFR3, G697C-FGFR3, N535K-FGFR4) and possesses the strongest kinase-inhibitory activity on N549H-FGFR2 (IC50 of 0.5 nM) among all FGFRs tested. We therefore investigated the effects of AP24534 on endometrial cancer cells harboring activating FGFR2 mutations and explored the underlying molecular mechanisms. AP24534 significantly inhibited the proliferation of endometrial cancer cells bearing activating FGFR2 mutations (N549K, K310R/N549K, S252W) and mainly induced G1/S cell cycle arrest leading to apoptosis. AP24534 also diminished the kinase activity of immunoprecipitated FGFR2 derived from MFE-296 and MFE-280 cells and reduced the phosphorylation of FGFR2 and FRS2 on MFE-296 and AN3CA cells. AP24534 caused substantial reductions in ERK phosphorylation, PLCγ signaling and STAT5 signal transduction on ECs bearing FGFR2 activating mutations. Akt signaling pathway was also deactivated by AP24534. AP24534 causes the chemotherapeutic effect through mainly the blockade of ERK, PLCγ and STAT5 signal transduction on ECs. Moreover, AP24534 inhibited migration and invasion of endometrial cancer cells with FGFR2 mutations. In addition, AP24534 significantly blocked anchorage-independent growth of endometrial cancer cells. We, for the first time, report the molecular mechanisms by which AP24534 exerts antitumor effects on ECs with FGFR2 activating mutations, which would provide mechanistic insight into ongoing clinical investigations of AP24534 for ECs.